Penerapan Sistem Informasi Manajemen pada PT. Prima Indonesia Logistik - Alacsel, Sanjaya (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The purpose of the research is to give recommendations to PT. Prima Indonesia Logistics Belawan in the correct use of Management Information System. The research method is that this research is qualitatively descriptive. Logistics is the art and science of regulating and controlling the flow of goods, energy, information, and other resources, such as products, services, and people, from the source of production to the market in order to optimize the use of capital. A management information system is an operating system that performs a variety of functions to generate outputs that are useful to the operators and management of the organization concerned. So to get the right information system you need to pay attention to several elements, namely Competitive Advantage, Customer Value View, Uniqueness Angle, Time and Place, Smooth Transfer to Customer, Accuracy Benefit.